The Influence of the Problem Based Learning Model on Student Activity and Learning Outcomes in Business Economics Elements - Mila Ladia Facma; Zuwirna Zuwirna; Ramalis Hakim; Rayendra Rayendra (JETL (Journal of Education, Teaching and Learning), 2025)
The low level of student engagement and achievement in vocational economics learning necessitates the application of innovative instructional models. This study aims to examine the effect of the Problem Based Learning (PBL) model on student learning activity and outcomes in the Economic Business subject. A quasi-experimental design with a pretest-posttest control group was employed. The participants were 61 tenth-grade students from SMK Negeri 1 Painan, selected through purposive sampling. Data were collected using validated instruments: learning outcome tests and observation sheets. Descriptive and inferential statistics, including independent samples t-tests, were used for data analysis. Results show that the experimental group, which received PBL treatment, had significantly higher posttest scores (M = 89.90) and N-Gain (0.72) compared to the control group (M = 76.68; N-Gain = 0.35). Student activity in the experimental group also increased steadily across sessions. Statistical tests confirmed that the differences in both outcomes and activity were significant (p < 0.05). These findings support the effectiveness of PBL in promoting active learning and improving student achievement in vocational education